Oratory skill and its types ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Oratory skill, the art of effective public speaking, has been a crucial aspect of human communication since ancient times. This scientific article aims to explore the concept of oratory skill, its historical significance, and the various types of oratory skills that exist. By understanding the different types of oratory skills, individuals can enhance their public speaking abilities and effectively convey their message to diverse audiences.